JOURNAL OF GOVERNMENT & POLITICS : Assessing the Delayed Gratification, Identity Orientation and Transitional Plans of ESGP-PA Recepients: Implications for policies and Program Development - Alma G. Maranda , Antoniette Natonietta (FISIPOL UMY, 2016)
Governments in developing countries adopted the Conditional Cash Transfer (CCT)system to alleviate poverty and reduce the transmission of poverty from one generation to the next.